2021
DOI: 10.21763/tjfmpc.825045
|View full text |Cite
|
Sign up to set email alerts
|

Tip 2 Diyabetli Bireylere Mobil Telefonları Aracılığı ile Uzaktan Verilen Video Eğitimin Diyabetle İlgili Bilgi ve Alışkanlıklara Etkisi

Abstract: Objective: This study was conducted with the purpose of analysing the effect to diabetes related knowledge and habits of distance learning via videos through mobile phones in individuals with type 2 diabetes. Method: The universe of the study was composed of individuals with type 2 diabetes who were admitted to the diabetes polyclinic of Balikesir Atatürk City Hospital between July 2018-January 2019 whereas the sample group was composed of 100 individuals with Type 2 diabetes in total who met the inclusion cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Diabetes education is crucial in the rehabilitation of diabetes. Studies have shown that patients who received diabetes education improved their ability to manage the disease and their attitudes towards it (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes education is crucial in the rehabilitation of diabetes. Studies have shown that patients who received diabetes education improved their ability to manage the disease and their attitudes towards it (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the use of this telehealth approach contributes positively to the health outcomes of individuals, increases their quality of life (10), increases the level of knowledge about diabetes, decreases the rate of acute complications, increases regular blood glucose monitoring, decreases HbA1c level, increases compliance with treatment, diet compliance and regular exercise habits, and decreases diabetes-related stress (6,8,11). This study was planned to examine the effectiveness of remote education given via mobile phone to individuals diagnosed with Type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%